MicroRNA and their target mRNAs change expression in whole blood of patients after intracerebral hemorrhage. Issue 4 (April 2020) - Cheng, Xiyuan; Ander, Bradley P; Jickling, Glen C; Zhan, Xinhua; Hull, Heather; Sharp, Frank R; Stamova, Boryana
Previous studies showed changes in mRNA levels in whole blood of rats and humans, and in miRNA in whole blood of rats following intracerebral hemorrhage (ICH). Thus, this study assessed miRNA and their putative mRNA targets in whole blood of humans following ICH. Whole transcriptome profiling identified altered miRNA and mRNA levels in ICH patients compared to matched controls. Target mRNAs of the differentially expressed miRNAs were identified, and functional analysis of the miRNA-mRNA targets was performed. Twenty-nine miRNAs (22 down, 7 up) and 250 target mRNAs (136 up, 114 down), and 7 small nucleolar RNA changed expression after ICH compared to controls (FDR < 0.05, and fold change ≥ |1.2|). These included Let7i, miR-146a-5p, miR210-5p, miR-93-5p, miR-221, miR-874, miR-17-3p, miR-378a-5p, miR-532-5p, mir-4707, miR-4450, mir-1183, Let-7d-3p, miR-3937, miR-4288, miR-4741, miR-92a-1-3p, miR-4514, mir-4658, mir-3689d-1, miR-4760-3p, and mir-3183. Pathway analysis showed regulated miRNAs/mRNAs were associated with toll-like receptor, natural killer cell, focal adhesion, TGF-β, phagosome, JAK-STAT, cytokine–cytokine receptor, chemokine, apoptosis, vascular smooth muscle, and RNA degradation signaling. Many of these pathways have been implicated in ICH. The differentially expressed miRNA and their putative mRNA targets and associated pathways may provide diagnostic biomarkers as well as point to therapeutic targets for ICH treatments in humans.